A note on continuous catalytic hydrodemetallization of heavy oils - Mayorga, José; Montoya, Rubén (Rev. Téc. Fac. Ing. Univ. Zulia)
In this work, the continuous catalytic hydrodemetall1zation of a heavy crude of from the Orinoco OU Belt was studied in a fixed-bed reactor. Using a fractional factorial design, the effects of hydrogen pressure, temperature, hydrogen/crude ratio. crude spatial time and catalysts on vanadium removal, API gravity and viscosity were evaluated. lt was found that temperature and spatial time have a significant effect on the devanadization percentage. the catalyst on API gravity and temperature on viscosity.